Impact of Employee Selection on Work Productivity: (Case Studi At PT. Prima Alloy Steel Universal Gedangan Sidoarjo) - Achmad Daengs GS; Enny Susanti; Rina Dewi; Retno Susanti; Ramansyah Hidayat (International Journal of Economics and Management Sciences, 2025)
Prima Allioy Steel Universal Gedangan is a company operating in the field of steel. Every year this PT carries out selection of new employees. To find out whether the addition of employees will reduce productivity, research is needed entitled "THE INFLUENCE OF EMPLOYEE SELECTION ON WORK PRODUCTIVITY AT PT. PRIMA ALLOY STEEL UNIVERSAL GEDANGAN ". This research data was taken from employee selection data in 2006 and 2007 and actual production data during that year. This data is then processed with regression and correlation analysis as well. From the regression analysis that has been carried out, it can be seen that the more new employees who pass the selection, the more their productivity will decrease. This happens because the coefficient value of new employee acceptance has a negative sign. From the correlation obtained, it can be seen that the relationship between new employee recruitment selection and productivity is 54.8%.